(untitled) (The Macau Ricci Institute Journal, 2023)
ABSTRACTThis article presents the approach of our investigation into the Chinese wisdom tradition and its role in developing a code of ethics in pivotal areas of social lives. The aim of our investigation is to contextualise Chinese wisdom and ethical traditions to inform those who are interested or engaged in a “dialogue” with China, regarding the dynamics and key strands of the tradition for their reference in dealing with this cross-cultural dialogue. Key words: Chinese wisdom traditions, practical ethics, contextualisation